The Phytochemical Ingredients and Therapeutic Potential of Cynara scolymus L. - Sanjay Agarwal (Mazandaran University of Medical Sciences, 2021)
Background: Medicinal herbs remain a vital source of new chemical entities, instead of the attempt of pharmaceutical companies using combinatorial and synthetic chemistry techniques for developing new drugs. Objectives: The primary aim of review is to highlight the different phytochemcial ingredients and their therapeutic potential in Cynara scolymus Methods: Cynara scolymus, commonly known as artichoke is a rich source of polyphenolic compounds, mainly caffeoylquinic acids and flavonoids, isolated in the polar extracts of the plant, together with the polysaccharide inulin. The worldwide scientific databases were comprehensively and systematically reviewed and summarized. Results: The beneficial effects of artichoke in experimental studies include antidiabetic, anti-obesity, anti-inflammatory, anti-hypercholesterolemic, hepatoprotective, nephroprotective, gastrointestinal protectant, reproductive, and anticancer properties. Studies with artichoke conducted in experimental animals reported no mortality or significant toxicity. Increasing attention is being paid to developing herbal medicines as a newly emerging treatment for the welfare of the patients in the last few decades. Conclusion: The present review detailed the versatile therapeutic efficiency and diverse application of C. scolymus. This medicinal herb has been appropriately used in conventional medicine for a long and helps cure various ailments.